2018
DOI: 10.1007/s00248-017-1140-6
|View full text |Cite
|
Sign up to set email alerts
|

Ectoparasite Activity During Incubation Increases Microbial Growth on Avian Eggs

Abstract: While direct detrimental effects of parasites on hosts are relatively well documented, other more subtle but potentially important effects of parasitism are yet unexplored. Biological activity of ectoparasites, apart from skin injuries and blood-feeding, often results in blood remains, or parasite faeces that accumulate and modify the host environment. In this way, ectoparasite activities and remains may increase nutrient availability that may favour colonization and growth of microorganisms including potentia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 68 publications
(78 reference statements)
0
11
0
Order By: Relevance
“…Avian reproductive strategies and overall reproductive success are probably under the strong selective pressure of environmental microorganisms. Recent studies have found bacterial density on the eggshell to be the main precursor of hatching failure across avian species (Lee et al, 2017;Peralta-Sanchez et al, 2018;Tomas et al, 2018). These findings are not surprising given that previous studies documented that microbes are able to pass through the eggshell into the egg interior and negatively affect embryo viability (Bruce and Drysdale, 1994;Pinowski et al, 1994;Cook et al, 2003;Fonseca et al, 2011;Hansen et al, 2015) or hatchling phenotype (Javurkova et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Avian reproductive strategies and overall reproductive success are probably under the strong selective pressure of environmental microorganisms. Recent studies have found bacterial density on the eggshell to be the main precursor of hatching failure across avian species (Lee et al, 2017;Peralta-Sanchez et al, 2018;Tomas et al, 2018). These findings are not surprising given that previous studies documented that microbes are able to pass through the eggshell into the egg interior and negatively affect embryo viability (Bruce and Drysdale, 1994;Pinowski et al, 1994;Cook et al, 2003;Fonseca et al, 2011;Hansen et al, 2015) or hatchling phenotype (Javurkova et al, 2014).…”
Section: Introductionmentioning
confidence: 94%
“…Egg-laying animals can initially inoculate eggs in ovo, as seen in five bird species and one lizard species (Ruiz-Rodríguez et al, 2018;Trevelline et al, 2018). For birds, the egg environment in the nest is relatively sterile and inoculation at this stage depends on temperature, humidity, nest hygiene (reviewed in D'Alba and Shawkey, 2015), and ectoparasites (Tomás et al, 2018). Once chicks are hatched, the food fed by parents is likely to further inoculate the gut microbiome (Ruiz-Rodríguez et al, 2018); therefore horizontal transmission of microbes is likely to have a strong effect on gut microbiome diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Parental and breeding activity, as well as nest material and ectoparasites, determine bacterial environment of nesting cavities and of eggshells (González-Braojos et al 2012, Peralta-Sánchez et al 2012, Grizard et al 2015, Tomás et al 2018. These bacteria can have positive, negative or no effects on the offspring (Singleton and Harper 1996, Moreno et al 2003, González-Braojos et al 2012, Soler et al 2017, Devaynes et al 2018.…”
Section: Introductionmentioning
confidence: 99%